Improving Patient Outcomes in the Dual Crises of Climate Change and COVID-19: Proceedings of the Third Annual Clinical Climate Change Meeting, January 8, 2021. Issue 11 (5th November 2021) - Senay, Emily; Bernstein, Aaron; Shephard, Peggy; Salas, Renee; Rizzo, Albert; Sherman, Jodi D.; Richardson, Lynne; Butts, Gary; Marwah, Harleen; Solomon, Caren; Galvez, Maida; Thanik, Erin; et al.
Abstract : : The tremendous global toll of the COVID-19 pandemic does not fall equally on all populations. Indeed, this crisis has exerted more severe impacts on the most vulnerable communities, spotlighting the continued consequences of longstanding structural, social, and healthcare inequities. This disparity in COVID-19 parallels the unequal health consequences of climate change, whereby underlying inequities perpetuate adverse health outcomes disproportionately among vulnerable populations. As these two crises continue to unfold, there is an urgent need for healthcare practitioners to identify and implement solutions to mitigate adverse health outcomes, especially in the face of global crises. To support this need, the 2021 Clinical Climate Change Conference held a virtual meeting to discuss the implications of the convergence of the climate crisis and COVID-19, particularly for vulnerable patient populations and the clinicians who care for them. Presenters and panelists provided evidence-based solutions to help health professionals improve and adapt their practice to these evolving scenarios. Together, participants explored the community health system and national solutions to reduce the impacts of COVID-19 and the climate crisis, to promote community advocacy, and foster new partnerships between community and healthcare leaders to combat systemic racism and achieve a more just and equitable society.